2007
DOI: 10.1016/j.ergon.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Estimating upper limb discomfort level due to intermittent isometric pronation torque with various combinations of elbow angles, forearm rotation angles, force and frequency with upper arm at 90° abduction

Abstract: Industrial jobs involving upper arm abduction have a strong association with musculoskeletal disorders and injury. But there is still paucity of data on the different risk factors that are responsible for the genesis of such disorders or injuries. The current laboratory study is an attempt that direction. Thirty-six right-handed male university students participated in a full factorial model of three forearm rotation angles (60% prone Relevance to industryThere is still a paucity of data on risk factors for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…MVC grip force has been discussed: Kattel elbow flexion at 135° was significantly different from that with the elbow at 90° and 180° [1]. Mukhopadhyay et al also reported there was no difference in discomfort between 90° and 135°, but at 45° it was significantly different from the other two angles [29]. For forearm rotation, all three angles were significantly different from each other.…”
Section: Elbow Flexion Anglementioning
confidence: 91%
See 2 more Smart Citations
“…MVC grip force has been discussed: Kattel elbow flexion at 135° was significantly different from that with the elbow at 90° and 180° [1]. Mukhopadhyay et al also reported there was no difference in discomfort between 90° and 135°, but at 45° it was significantly different from the other two angles [29]. For forearm rotation, all three angles were significantly different from each other.…”
Section: Elbow Flexion Anglementioning
confidence: 91%
“…Then, the participant was asked again to press up to maximum grip after a minimum recovery time of 2 min or until he felt no discomfort. The recovery time was set according to O'Sullivan and Gallwey [30] and Mukhopadhyay et al [29]. The greater of the two was recorded as the MVC grip for that particular treatment condition for the participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tasks selected were identified as routine electrical activities during the field study. Participants were instructed to perform each task for a period of 5 minutes followed by a rest period of 5 minutes between tasks, as per Gallwey (2002, 2005) and Mukhopadhyay et. al.…”
Section: Methodsmentioning
confidence: 99%
“…Others have completed laboratory based discomfort studies of simulated tasks to study wrist, forearm and shoulder posture effects Gallwey, 1999, 2002;O'Sullivan and Gallwey, 2005;Mukhopadhyay et al, 2007;Khan et al, 2009). Further research studies are necessary performing these types of simulated tasks for longer durations than five minutes to ensure the findings reflect the actual cumulative fatigue effects as experienced in the course of a working day.…”
Section: Limitationsmentioning
confidence: 99%